PRIORITY OF TAXES UNDER THE BANKRUPTCY ACT. - Kunze, Harry L. (The Accounting Review, 1936)
Abstract The financial statement of affairs, when used exhibits the assets of a bankrupt business classified according to the various claims the creditors have to the assets. The article discusses priority of taxes under Section 64 of the Bankruptcy Act. It says that the court shall order the trustee to pay all taxes legally due and owing by the bankrupt to the U.S. state, county, district, or municipality, in the order of priority as set forth in paragraph, provided, that no order shall be made for the payment of a tax assessed against real estate of a bankrupt in excess of the value of the interest of the bankrupt estate therein as determined by the court. Moreover, the debts will have priority, in advance of the payment of dividends to creditors, and will be paid in full out of bankrupt estates. The order of payment shall be cost of preserving the estate, filing fees, and expenses incurred in recovering transferred or concealed property, cost of administration, expense of opposing composition, wages earned within three months prior to bankruptcy, not to exceed $600 to each claimant, taxes payable and debts entitled to priority under state or federal law.